Real-world data of pyrotinib-based therapy for patients with brain metastases of HER2-positive advanced breast cancer: a single-center retrospective analysis and molecular portraits - Wang, Hui; Liu, Qiaoyan; Zhang, Mi; Zhang, Juan; Ran, Ran; Ma, Yingying; Yang, Jiao; Wang, Fan; He, Shujuan; Zhao, Xiaoai; Wang, Le; Zhang, Lingxiao; et al. (Frontiers in Oncology, 2023)
Introduction: Pyrotinib is a novel irreversible pan-HER tyrosine kinase inhibitor (TKI). However, real-world data of pyrotinib-containing therapy in human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) and developing brain metastases (BM) is limited, and the genomic profile of this subpopulation is almost undefined. Methods and Materials: Patients with BM of HER2-positive MBC (n=35) treated with pyrotinib-containing therapy were enrolled in this analysis. Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and toxicity profiles were conducted. Hazard ratios (HRs) and 95% confidence intervals (CIs) for disease progression were estimated using Cox proportional hazards models. Targeted next-generation sequencing of 618 cancer-relevant genes was performed on plasma and primary breast tumors from patients with BM and without BM. Results: The median PFS time was 8.00 (95%CI, 5.98–10.017) months and the median OS time was 23 (95%CI, 10.412–35.588) months. The ORR was 45.7% and the DCR was 74.3%. In the Cox multivariate analysis, prior exposure to brain radiotherapy (HR=3.268), received pyrotinib as third or higher-line treatment (HR=4.949), subtentorial brain metastasis (HR=6.222), and both supra and subtentorial brain metastasis (HR=5.863) were independently associated with increased hazard of progression. The frequent 3-4 grade adverse events were increased direct bilirubin (14.3%), and 2 patients suffered from 3-4 grade diarrhea. In the exploratory genomic analysis, altered frequencies of FGFR3, CD276, CDC73, and EPHX1 were higher in the BM group. The consistency of mutated profiles of plasma and primary lesion in BM group was significantly lower (30.4% vs. 65.5%; P=0.0038). Conclusions: Pyrotinib-containing therapy shows favorable effectiveness and tolerable safety in patients with BM of HER2-positive MBC, particularly in population with brain radiotherapy-naive, received pyrotinib as first or second-line treatment, and developed supratentorial brain metastasis. In exploratory genomic analysis, patients with BM showed distinct genomic features from patients without BM.